The Mishnah in Contemporary Perspective : Part Two. - Neusner, Jacob; Avery-Peck, Alan. (Boston : BRILL, 2006)
This second volume of a two-part project displays the best of contemporary Israeli, North American, and European scholarship on the Mishnah, revealing the intellectual vitality of scholarship in all three centers of learning. Because of the many viewpoints included here, it is the most representative selection of contemporary Mishnah-study available in any collection in a Western language.
Intro -- The Mishnah in Contemporary Perspective -- CONTENTS -- Preface -- Anecdotal Evidence: The Yavneh Conundrum, Birkat Hamminim, and the Problem of Talmudic Historiography -- On the Quality of the Rabbinic Text: The Opening of the Mishnah -- The Construction of Households in the Mishnah -- The Mishnah in Historical and Religious Context -- The Structure and Implicit Message of Mishnah Tractate Nazir -- Archaeology and the Mishnah's Halakhic Tradition: The Case of Stone Vessels and Ritual Baths -- The Poetics of the Mishnah -- Why We Cannot Assume the Historical Reliability of Attributions: The Case of the Houses in Mishnah-Tosefta Makhshirin -- Subject Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Mishnah-Criticism, interpretation, etc.-History.; Electronic books